Two-dimensional imine-based covalent–organic-framework derived nitrogen-doped porous carbon nanosheets for high-performance lithium–sulfur batteries. (28th April 2021) - Guo, Chaofei; Xu, Jiaojiao; Lv, Li-Ping; Chen, Shuangqiang; Sun, Weiwei; Wang, Yong
Abstract : COF-derived nitrogen-doped porous carbon nanosheets with S loading achieve high capacities and good long-cycling performance for lithium–sulfur batteries. Abstract : Lithium–sulfur batteries are attracting more attention due to their high theoretical capacity and energy density. However, they have the problems of short cycling performance, low sulfur loading and shuttle effect; in order to overcome these problems, more efforts have been devoted to the exploration of effective host materials for sulfur confinement. Herein, we report a facile approach for the synthesis of nitrogen-doped porous carbon (NPC) nanosheets, derived from imine-based covalent organic frameworks (COFs), as the host material. In situ nitrogen doping is very uniform due to the inherited nitrogen element distributed uniformly in the COF skeleton. Sulfur-loaded NPC composites can achieve a high sulfur loading amount of 71.8% and enhanced lithium–sulfur battery performance, in terms of a high initial discharge capacity (1398 mA h g −1 at 0.1C) and good cycling properties (reversible capacity of 833 mA h g −1 after 250 cycles). The existence of nitrogen doped carbon nanosheets with a high surface area and controlled porosity can lead to effective immobilization of the polysulfides and simultaneous improvement of the reaction kinetics of the sulfur species. This design strategy provides an extended method for fabricating high performance cathodes for lithium–sulfur batteries.